MENERJEMAHKAN “RANTAU DEN PAJAUH”: PERUBAHAN MAKNA BUDAYA DAN IDEOLOGI TERJEMAHAN DALAM TERJEMAHAN AI GOOGLE - Yulia Oktafia Jasman; Veni Roza; Widya Syafitri (Universitas Mahaputra Muhammad Yamin, 2026)
This study examines translation ideology and cultural meaning shifts in the Minangkabau song Rantau Den Pajauah translated into English using Google Translate. The study used a qualitative descriptive method with 20 lyric lines as the primary data. Each source line was compared with its English output and classified using Molina and Hurtado Albir’s translation technique framework, cultural meaning shift analysis, and Venuti’s concepts of domestication and foreignization. The findings show that literal translation is the most frequent technique, appearing in 7 of 20 lines. Adaptation appears in 5 lines, while modulation and equivalence each appear in 4 lines. The analysis also shows that culturally specific expressions such as rantau, uda, harato, anak dagang, kasiah, and cinto undergo cultural reduction, semantic simplification, and partial weakening of metaphorical meaning. Ideologically, the translation tends toward domestication because Google Translate generally converts Minangkabau cultural expressions into more familiar English expressions. The study concludes that Google Translate can produce readable translations, but it still requires human post-editing to preserve cultural meanings in literary and regional song translation